Macrogeographic genetic variation in broad-snouted caiman (Caiman latirostris) - Schmidt Villela, Priscilla Marqui (2008)
Broad-snouted caiman's (Caiman latirostris) geographic distribution comprises one of the widest latitudinal ranges among all crocodilians. In this study we analyzed the relationship between geographic distance (along the species latitudinal range) and genetic differentiation using DNA microsatellite loci developed for C. latirostris and Alligator mississippiensis. The results suggest that there is a consistent relationship between geographic distance and genetic differentiation; however, other biogeographical factors seem to be relevant. The Atlantic Chain (Serra do Mar) seems to be an effective geographic barrier, as well as the relatively narrow (≤1.5 km) sea channel between Cardoso Island and the continent. In addition, coastal populations seem to have been well connected in recent geological time (Pleistocene 16,000 years ago) all along the eastern Brazilian coast. Further studies should focus on the São Francisco River drainage, which is still poorly known for this species.